Temperature Dependent Ultrasonic Study in Scandium Antimonide Semiconductor - A. K. Gupta; S. Srivastava; K. B. Thapa (E-Journal of Chemistry)
In this paper analysis of wave propagation of elastic wave in scandium antimonide semiconductor was investigated. In scandium antimonide semiconductor, NaCl structure was found. Ultrasonic properties like ultrasonic attenuation, sound velocities, acoustic coupling constants, and thermal relaxation time have been investigated in cubic scandium antimonide semiconductor. Second and third order elastic constant have been computed for the evaluation of above said ultrasonic properties. Second and third elastic constant was studied at the various temperatures. Longitudinal and shear velocity was calculated by using the elastic constant. Longitudinal and shear velocity increase with increase the temperature. Ultrasonic attenuation either from longitudinal or shear wave propagation in cubic materials increase with increase the temperature.